Moderate Dai in the Era of Digitalization; Challenges and Ethics of Preaching on Social-Media According to Islam and Local Wisdom - Ridho, Hilmi; Sabil, Afif (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
Nowadays, the phenomenon of proselytizing through social media has become a demand and trend in itself. One of its advantages is that the Internet network can penetrate the boundaries of space and time. However, its existence also raises pros and cons among the community. In reality, all da'wah content on social media is not acceptable, and it often reaps controversy, causes polemics, and triggers conflict. For example, political da'wah that contains hate speech, economic da'wah that contains elements of forced alms, business da'wah that aims to promote a product, and so on. This research is a literature review that adopts mostly qualitative research techniques. The main data sources are scientific literature studies in the form of books, yellow books, and journals that discuss challenges and ethical values in preaching on social media. The purpose of this study is to examine the extent of the problems and challenges of da'wah in social media, given the rapid advancement of technology and information, of course, da'wah will certainly experience new transformations and challenges by the times. In addition, it wants to know how the ethics of a preacher on social media should be in delivering his da'wah material, both to the people present and netizens in the view of Islam and local wisdom.